Patienterna vid sinnessjukhuset för fångar - Matti I. Joukamaa; Vilho J. Mattila; Raimo K. R. Salokangas; Vilho I. Jäppinen; Lauri Salmi; Hannu Holm (Nordisk Tidsskrift for Kriminalvidenskab)
See abstract in article.